PERANCANGAN PROGRAM APLIKASI HIDROGRAF SATUAN SINTESIS (HSS) DENGAN METODE GAMA 1, NAKAYASU, DAN HSS ITB 1 - Enung, Enung (Potensi : Jurnal Sipil Politeknik, 2016)
This paper present about design of Â Unit hydrographs (UH) application program using three methods of Synthetic Unit Hydrograph namely Gama 1, ITB 1, and Nakayasu. Unit hydrographs are either determined from gauged data or derived using empirically-based synthetic unit hydrograph procedures. In Indonesia, the discharge records may not be available either for several locations or for long time scales, and therefore synthetic unit hydrographs are crucial in flood and water re-sources management. Computer programs were developed to provide a means for rapid analysis. of rainfall and run off data. The purpose of this research is to design computer application program analysis based on three methods of Synthetic Unit Hydrograph namely Gama 1, ITB 1, and Nakayasu. This computer application program use Visual Basic 6.0 as the programming language. This research began from literature studies, lay out design of the display program, the developed of the algorithm, and then carried out using the programming language Visual Basic program, then perform verification and validation program using secondary data. The accomplished results show that computer application program namely Synthetic Unit Hydrograph Program can be used to analyze unit hydrograph which show in table and graph.